Associated Factors that Supporting Toilet Training for Children with Intellectual Disabilities: A Systematic Review - Jaleha, Siti; Hufad, Achmad; Aprilia, Imas Diana; Sunardi, Sunardi (Department of Special Education, 2024)
The basic aspect that must be mastered by children with intellectual disabilities before mastering other self-development skills is doing toilet training independently. Learning for children with intellectual disabilities in carrying out toilet training activities requires a separate technique and needs to pay attention to the factors that support the success of the program. This study aims to describe the associated factors that support toilet training for children with intellectual disabilities. This study uses a qualitative approach with a type of literature review research that seeks to describe the related factors that support toilet training for children with intellectual disabilities. This literature review was conducted from August to December 2022 using PRISMA. The authors conducted searches in online databases with large repositories of academic studies and fully accessible by the authors. The results showed that: (1) the toilet training program was made based on the results of an assessment containing the abilities, needs, and potential of children with intellectual disabilities, (2) knowledge and intervention skills possessed by parents provide a great opportunity for successful toilet training for children , and (3) there is collaboration between parents and teachers regarding the implementation of toilet training. The success of toilet training for children with intellectual disabilities is influenced by many factors so that the toilet training process requires intensive assistance, especially for parents.